EFFECTIVENESS OF INDIGENOUS ENDOMYCORRHIZAL BIOFERTILIZER PROTOTYPE ON ORGANIC SALAK (Salacca zalacca) PLANTATIONS AND ITS EFFECT ON NUTRIENT AND CARBOHYDRATE CONTENT OF LEAVES - I Nyoman Rai; I Ketut Suada; I Wayan Wiraatmaja; Ni Komang Alit Astiari (SEAMEO BIOTROP, 2021)
Organically cultivated salak (Salacca zalacca) on dry land has limited production in Bali. Typically, fertilization is carried out using leaf litter or other organic fertilizers because soil fertility is low for salak plantations. The present study analyzed the effectiveness of an indigenous endomycorrhizal biofertilizer on the nutrient and total carbohydrate content of salak leaves and fruits. The study used a randomized block design with nine replicates. The treatment consisted of three levels, i.e., (1) fertilization with leaf litter only, as practiced by farmers and used as the control (C); (2) fertilization with an indigenous endomycorrhizal biofertilizer prototype (P); and (3) combined fertilization with leaf litter and an indigenous endomycorrhizal biofertilizer prototype (PM). Spores of indigenous endomycorrhizae from salak plantations were used to prepare the biofertilizer prototype. The results showed that the P and PM treatments provided beneficial results, such as: (1) significantly increasing chlorophyll content, relative water content of leaves, and the number and weight of fruits per tree; (2) improving fruit quality by increasing sweetness and weight per fruit; and (3) having a positive effect on water uptake and nutrient absorption, as indicated by high N and P contents in leaf tissue and high carbohydrate content in leaves.